Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Sustainable tea production in western Sichuan: Defining optimal soil pH threshold to balance rhizosphere bacterial communities and flavor metabolites - Haojie Cao; Ning Ma; Siyu Wang; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu; Xiaoxun Xu; Guiyin Wang (Applied Soil Ecology, 2026)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Characterizing NH3 emissions from a sheep feedlot and a manure composting facility in North China with the inverse dispersion technique - Chunjing Liu; Wenhua Liao; Yishuo Xu; Di Wu; Zhiling Gao; Jianzhi Xie (Agricultural and Forest Meteorology, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image